PENGEMBANGAN VIDEO PEMBELAJARAN MEMPERBANYAK TANAMAN DENGAN SAMBUNG PUCUK UNTUK SISWA SMK - H. S., Budi Prasetyanto; Asyhar, Rayandra -; -, Asrial - (Program Magister Teknologi Pendidikan Universitas Jambi, 2011)
The present research is aimed to develop learning video used as an instruction media of plant propagation with scion grafting. Principles of social learning, contructivism, and behavioral theories are applied underpinning the model development in this research. Adaptation of Dick and Carey’s model (1985) is used as media development, whereas in the subject-matter development is used Warsihna’s model (2010). The study reveal that the developed media has a good quality in guiding students in the instructional process, especially in the subject of Plant Propagation with Scion Grafting. Based on observation and experts’ judgment, it also can be said that the media is very helpful and interesting to use in the classroom. Keywords: intructional video media, scion grafting, plant propagation